Sens et contresens: l'étude de la culture matérielle au Québec - Mousette, Marcel (Ethnologies, 1982)
AbstractThis article outlines the author's approach to the study of human behavior from the standpoint of common material objects in everyday use. Drawing from previous research in the area of material culture, he attempts to establish the determining factors that have contributed to the présent state of studies in this area.